flat assembler
Message board for the users of flat assembler.
Index
> Heap > Numerical oddities Goto page Previous 1, 2, 3 ... 5, 6, 7 ... 24, 25, 26 Next 
Author 

revolution
sleepsleep wrote: emm, i would like to use my first helping tools. i need some hint. 

24 Jan 2009, 19:28 

Borsuc
Why nonsensible? pi has nothing to do with it. You can put there y and you arrive at the conclusion that x=y if you take the positive root (pi just a random variable here...)
_________________ Previously known as The_Grey_Beast 

24 Jan 2009, 20:52 

sleepsleep
well, borsuc.
if 2x = y + 3 is ==> y = 2x 3 then how come y = 3 in the end. 

24 Jan 2009, 21:11 

Borsuc
2x = y + 3
x = 3 y = 3 ==> 2*3 = 3 + 3 6 = 6 x=y (y, no matter what it is! there's nothing special here about 'pi') 

25 Jan 2009, 01:09 

sleepsleep
if you change x=4 and y = 5
so 2(4) = 5+3 it will count correct until this line. 3  x = y  x 

25 Jan 2009, 01:22 

revolution
Borsuc wrote: (pi just a random variable here...) 

25 Jan 2009, 08:31 

nop
Code: If x = (a + n) / 2 ;x is the average of 2 constants a, n then 2x = a + n and 2x(a  n) = a^2  n^2 ;multiply by the difference of a and n so a^2  2x(a  n)  n^2 = 0 => a = n ;is only valid if a = n i.e. a  n = 0 e.g. x = (p + 3) / 2 ..... ..... => p = 3 = x x = (q + 4) / 2 ..... ..... => q = 4 = x 

25 Jan 2009, 09:57 

revolution
nop: Can you formulate that into an answer? I'm not 100% clear about what you imply.


25 Jan 2009, 10:03 

nop
revolution wrote: nop: Can you formulate that into an answer? I'm not 100% clear about what you imply. 

25 Jan 2009, 10:11 

revolution
nop wrote: that is my answer, just gimme the star dammit i need that star its all i've ever wanted pleeze just one little star <beg> <beg> <sob> <sob> I would be very happy to give you the star, but you must work hard for it (they are expensive and thus not given freely). Your "answer" above is not correct, sorry no star just yet! 

25 Jan 2009, 10:14 

nop
geez rev your too tough i worked relly hard finding that stuff on the net


25 Jan 2009, 10:44 

revolution
nop wrote: geez rev your too tough i worked relly hard finding that stuff on the net 

25 Jan 2009, 10:55 

sleepsleep
emm..
i think this line weird. 9  6x = pi^2  2pix 9  6x + x^2 = pi^2  2pix + x^2 it must be (9  6x) + x^2 = (pi^2  2pix) + x^2 so, this (3  x)^2 = (pi  x)^2 is invalid. because (9  6x) and (pi^2  2pix) must be solve first before integrate with x^2. well, if it is still incorrect, i wait for ur answer then. i like maths, but i am not doing so well with it. 

25 Jan 2009, 12:17 

revolution
sleepsleep: Keep trying.


25 Jan 2009, 12:21 

Borsuc
revolution wrote: Hehe, these days it seems there is no need to think anymore, what with the 'net available it has all the answers to the questions anyone could ever ask. Is it because of pi^2, that taking the square root means the absolute value of it? (not original number) I mean, when 'expanding' (pi + 3)(pi  3)  it only works the other way around? (otherwise it is absolute value) _________________ Previously known as The_Grey_Beast 

25 Jan 2009, 16:22 

revolution
The attempts so far seem to be sort of on the right track, but so far no one has yet been able to bring all the ideas together into a full coherent answer.
There are bits of an answer here and parts of an answer there etc. 

25 Jan 2009, 16:41 

sleepsleep
answer plez, it is over valentine already for God sake.


15 Feb 2009, 04:15 

revolution
sleepsleep wrote: answer plez, it is over valentine already for God sake. http://board.flatassembler.net/topic.php?p=82994#82994 (no answers yet) http://board.flatassembler.net/topic.php?p=83742#83742 (half solved) http://board.flatassembler.net/topic.php?p=88366#88366 (half solved) 

15 Feb 2009, 05:03 

windwakr
Ok, I'm probably wrong and looking stupid here but.....
If Pi does indeed equal 3, then on line 4 you would be dividing by zero to remove the (pi3), because (33)=0. Thus making the formula FALSE, right? Code: x = (pi + 3) / 2 x=(3+3)/2=3 2x = pi + 3 6=6 2x(pi  3) = (pi + 3)(pi  3) 0=6(0) 2pix  6x = pi^2  9 YOU DIVIDED BY ZERO TO REMOVE (pi3), the rest is just filler to make it look real 9  6x = pi^2  2pix 9  6x + x^2 = pi^2  2pix + x^2 (3  x)^2 = (pi  x)^2 3  x = pi  x pi = 3 I WANT ANOTHER STAR lol 

12 Aug 2009, 05:25 

Goto page Previous 1, 2, 3 ... 5, 6, 7 ... 24, 25, 26 Next < Last Thread  Next Thread > 
Forum Rules:

Copyright © 19992020, Tomasz Grysztar.
Powered by rwasa.